Antioxidant and polyphenol content of different Vitis vinifera seed cultivars and two facilities of production of a functional bakery product - Kapcsándi, Viktória (Chem Zvesti, 2021)
This study aimed to examine the differences between the antioxidant capacity, and the total polyphenol content of the seed of eight different grape varieties. We also attempt to create a functional loaf enriched with grape seed meal. To achieve this goal, 3, 6, and 9% of the grape seed meal were added to the loaves made of bread flour and gluten-free flour mixture, and then the changes in their antioxidant and polyphenol content were examined. Based on the results, there were significant differences between the polyphenol and antioxidant content of grape seed varieties. The antioxidant content of the grape seeds varied between 228.50 mg AAE/g (94.80 mg TE/g) and 438.33 mg AAE/g (181.86 mg TE/g) in case of fatty samples, and between 176.29 mg AAE/g (41.24 mg TE/g) and 424.91 mg AAE/g (99.40 mg TE/g) in case of defatted samples. The total polyphenol content of the fatty samples changed between 91.16 and 221.81 mg GAE/g; in case of defatted samples, it ranged from 46.01 to 207.68 mg GAE/g. Rhine Riesling contained the greatest amount of these compounds. The functionality of loafs was confirmed by spectrophotometric analysis. Total polyphenol content ranged from 0.91 to 3.16 mg GAE/g in case of wheat loafs, and from 1.39 to 5.92 mg GAE/g in case of gluten-free loafs, while the total antioxidant content changed between 0.70 and 6.44 mg AAE/g in case of wheat loafs, and ranged from 2.55 to 9.75 in case of gluten-free loafs. GRAPHIC ABSTRACT: [Image: see text]